RUBRIQ: tools, services, and software to improve peer review. Issue 4 (1st October 2013) - STEMMLE, Laura; COLLIER, Keith
ABSTRACT: Rubriq is on a mission to put lost time back into research. We estimate that 15 million hours are lost each year to redundant peer review as papers get rejected and flow down the journal prestige pyramid. Rubriq uses an author‐pays model to facilitate fast, independent, and standardized peer review performed by three academic peers who are financially compensated for their efforts. Authors receive the reviews as well as a detailed journal recommendation report in 1–2 weeks. This service is designed to improve journal selection, supplement editorial reviews, and make peer review more portable between journals. The creation of the standardized scorecard is just the first phase of Rubriq's plans to improve the scholarly communication workflow. Through lessons learned over the past year, the Rubriq approach is evolving into a broader set of tools, software, and services designed to speed and improve the scholarly communication process.